Kolaborasi dan Refleksifitas dalam Penciptaan Representasi Etnografi Visual dalam Bentuk Film Dokumenter: Sebuah Pengalaman - Rhino Ariefiansyah; Hestu Prahara (Antropologi Indonesia, 2012)
Various endeavors to quest for ethnographic representation have been conducted to answer questions about authority and relationship between the ethnographer and its subject. This quest brought about issues of collaboration and reflexivity as important themes in the visual anthropology discourse. This paper is an effort to expose our experiences in doing anthropological research using documentary video. Collaboration, reflexivity and complicity are concepts that become our concern in a research project in Indramayu. What we did is a kind of possibility to create ethnographic representation through visual medium. Keywords: collaboration, reflexivity, ethnographic representation, documentary video